Introduction to quantitative EEG and neurofeedback - Evans, James R.; Abarbanel, Andrew (Academic Press, 1999)
Neurofeedback techniques are used as treatment for a variety of psychological disorders including attention deficit disorder, dissociative identity disorder, depression, drug and alcohol abuse, and brain injury. Resources for understanding what the technique is, how it is used, and to what disorders and patients it can be applied are scarce. An ideal tool for practicing clinicians and clinical psychologists in independent practice and hospital settings, this book provides an introduction to neurofeedback/neurotherapy techniques. Key Features * Details advantages of quantitative EEG over other systems like PET and SPECT * Gives details of QEEG procedures and typical measures * Describes QEEG databases available for reference * Recommends protocols for specific disorders/patient populations.